PENGEMBANGAN MEDIA VIDEOSCRIBE DENGAN MODEL PROBLEM BASED LEARNING di SDN 106838 JATI MULYO - Suerningsih; Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to produce a videoscribe media product with a problem-based learning model to improve student learning outcomes. This study found a lack of utilization of audio-visual-based learning media that supports the teaching and learning process in the classroom and teachers of SD Negeri 106838 Jati Mulyo had never used Videoscribe learning media. The method used in this study is the development method or Research and Development (R&D) using the ADDIE model. The results obtained from several expert validators, namely media experts got a feasibility score of 76.9%, material experts got a feasibility score of 85%, teacher responses got a feasibility score of 91.6%, and student responses got a feasibility score of 95.3%. Thus, videoscribe media with a problem-based learning model is very suitable for use in the learning process.